3D‐Structured Photodetectors Based on 2D Transition‐Metal Dichalcogenide. Issue 1 (11th December 2021) - Mawlong, Larionette P. L.; Ahn, Jong-Hyun
Abstract : 3D‐structured transition‐metal dichalcogenides (TMDCs) are attracting significant attention in the field of photodetection owing to their remarkable and superior electronic and optoelectronic properties. This review outlines the optical properties of graphene and TMDCs. The recent progress in 2D‐planar graphene and TMDC‐based photodetectors are discussed. In addition, the recent advances in the different types of 3D‐structured TMDCs and their heterostructures used in photodetectors are elaborated in detail. These 3D‐structured TMDC‐based photodetectors exhibit enhanced optoelectronic properties compared to 2D‐planar photodetectors. Finally, this review concludes with the latest developments in 3D‐structured graphene and TMDC‐based photodetectors, and discusses the present challenges and future prospects for high‐performance photodetectors. Abstract : This review highlights the recent advancement in the development of the 3D‐structured 2D transition metal dichalcogenides and their heterostructures employed in photodetectors, including the various types of 3D geometric structures and their advantages in exhibiting high photodetection performance used in many diverse applications.